Direct skeletal attachment prosthesis for the amputee athlete: the unknown potential. Issue 3 (September 2016) - Muderis, Munjed; Aschoff, Horst; Bosley, Belinda; Raz, Guy; Gerdesmeyer, Ludger; Burkett, Brendan
Abstract Lower limb amputees often experience complications with the use of conventional socket-type prostheses, which further reduce their already compromised ability to perform the activities of daily living, or to participate in sporting activities. During the last two decades, a new technology of direct skeletal attachment (osseointegration) of prosthesis to the femoral residuum has been developed. The aim of this research was to assess the implant design, surgery protocols, and functional testing of this new technology on the first 100 patients using the Integral Leg Prosthesis procedure. This new knowledge can guide future engineering developments of osseointegration within the sporting arena. Between 1999 and 2013, direct skeletal implantation was performed on 112 amputees, from two centres in Germany and Australia. From the experience of the surgical team, modifications were made to the implant design. This re-engineering of the implant has reduced the surgical revisions due to infection from 29 % with the early implant design down to 7 %. The functional testing of the 34 Australian cases were assessed pre- and 12 months post-implant with significant improvements of one complete K-scale; the Q-TFA measures increased (50.9–86.7), whilst the Timed Up and Go decreased significantly (12.43 s ± 3.89 to 8.03 s ± 2.80), and the 6 min walk increased (304.0–383.9 m). From these findings, osseointegration technology is realistically the way of the future for amputee athletes. Further refinement of the implant design and sports-specific functional testing are required to define the potential of this technology.